A new species of Melita Leach (Amphipoda: Melitidae) from oligosaline waters of Russian Far East - Labay, Vjacheslav S. (Zootaxa, 2003)
A new amphipod species, Melita nitidaformis sp. n., is described from oligosaline Tunaycha Lake of Sakhalin Island (Russian Far East). The new species belongs to the species group of Melita with spines on the dorsal side of urosome 2 (without teeth).